Effects of Lamellar Keratectomy and Intrastromal Injection of 0.2% Fluconazole on Fungal Keratitis - Xinying You; Jun Li; Suxia Li; Weiyun Shi (Journal of Ophthalmology)
Purpose. To evaluate effects of lamellar keratectomy and intrastromal injection of 0.2% fluconazole (LKIIF) on fungal keratitis. Methods. Data for 54 eyes of consecutive patients with fungal keratitis treated with LKIIF were retrospectively analyzed. The lesions in these eyes did not heal or were aggravated after antifungal chemotherapy for 7 days. The maximum lesion diameters were ≤5 mm and maximum depth was not more than half of full corneal thickness. Cases were followed up for at least 90 days. Results. Forty-six eyes were cured (85.2%). The wound healing times were 3–16 days and were less than 7 days in 28 cases (51.9%). In cured eyes, uncorrected visual acuity (UCVA) and best-corrected visual acuity (BCVA) were both 20/250–20/20. The UCVA improved in 38 eyes and was unchanged in seven eyes. BCVA improved in 44 eyes and was unchanged in two eyes. When followed up for more than 90 days, 89% (41 of 46 eyes) showed improvement in UCVA and 11% were unchanged. Regarding BCVA, 98% improved and one eye was unchanged. No other complications were observed except neovascularization in one eye and thinner corneas. Conclusions. LKIIF was quick and effective for small fungal keratitis confined to half of the corneal thickness.